Subcutaneous abatacept in rheumatoid arthritis: A real-life experience (2019)
Objectives: To assess the effectiveness, safety, and drug survival of subcutaneous (SC) abatacept (ABA) in a cohort of rheumatoid arthritis (RA) patients in a real-world setting. Methods: This was a retrospective cohort study from 2014 to 2018 in which patients with RA (1987 ACR criteria) were included. Patients were evaluated at a single rheumatology outpatient center in Bogot a, Colombia. The patients were classified according to their treatment background: biological-naïve (n ¼ 65), switched from IV to SC ABA administration (125 mg-wk) (n ¼ 32), and inadequate response to biological DMARD (n ¼ 62). The pri- mary endpoint was a change in DAS28-CRP and RAPID3 from baseline to 12 months. A linear mixed effect model was used to correlate repeated measures. Adverse events were assessed and recorded during each visit to the rheumatology center. Several Cox proportional hazard regression models were used to test if there were any differences in drug survival curves based on seropositivity for rheumatoid factor (RF), and anti-Cyclic Citrulli- nated Peptide Antibodies (anti-CCP). Statistical analysis was done using software R version 3.4.4. Results: A total of 159 patients were included. Baseline characteristics of patients were as follows: female gender 84%, median age of 54 years (IQR 16), median disease duration 10 years (11), RF positive 96%, anti-CCP positive 89%, erosive disease 55%, median DAS28-CRP 5.0 (2), and median RAPID3 17 (10). Concomitant use of methotrexate and SC ABA monotherapy were reported at 52% and 30% respectively. Demographics and disease characteristics were similar for all groups, except for baseline DAS28-CRP, and RAPID3 in the group that switched route of administration. The interaction between time and group was significant (p ¼ 0.0073) for RAPID3. In- fections, constitutional symptoms, and headaches were the most frequent AEs. Retention rate corresponded to 60% at 48 months. The most frequent reason for drug suspension was loss of efficacy. Median time of treatment for SC ABA was 31 months (IQR 30). The only association that reached statistical significance was anti-CCP concentration [Q1–Q4] (p ¼ 0.005). According to the Cox proportional hazard regression model, there were significant differences between survival curves for Q1 (HR 0.15; 0.03–0.64 95% CI; p ¼ 0.0096), and Q2 (HR 0.28; 0.08–0.92 95% CI; p ¼ 0.0363) compared to the seronegative group. Conclusions: The results showed an improvement in RA disease activity and physical function in patients under SC ABA treatment. Patients switching from IV to SC administration of ABA had lower activity and functional impairment at baseline. SC ABA demonstrated a good safety profile consistent with previously published data. Patients with baseline levels of anti-CCP antibody concentrations had better drug survival than seronegative patients.